Cigarette butts and waste coffee grounds as additives to brick clay - Jovanović, Marina, inženjerka metalurgije (Array, 2020)
The paper analyses the influence of cigarette butts and waste coffee grounds addition on the properties of the brick clay. The waste materials were added to the clay in amounts of 5 wt.% and 10 wt.%. Standard consistency, plasticity, drying and firing behaviour and refractoriness were tested on the clay sample and the samples with wastes additions. Apparent density, apparent porosity, water absorption, strength and thermal conductivity were investigated on the samples fired at 1173 K. Addition of the waste materials improved thermal insulation characteristics and drying shrinkage, while other properties remain within the required limits for brick industry.